Design of high performance badminton shuttlecocks : virtual and rapid prototyping approach - Lin, Calvin S. H. (2013)
In this paper, a framework utilising virtual and rapid prototyping to aid design of a shuttlecock skirt was proposed and implemented. A standard template for flow simulation on ANSYS® CFX was developed to predict the aerodynamic performance of the virtual prototypes, with focus on reduced simulation time and complexity. This forms the basis of the computer aided design model – computational fluid dynamics – performance evaluation loop in the proposed framework. Steady state flow simulation was conducted for three simple computer aided design models of shuttlecocks, with different gap dimensions on the skirt. Wind tunnel drag study of the models reproduced through rapid prototyping validated the simulation result. The proposed methodology can also be applied to the existing design process for integration of virtual and rapid prototyping to reduce the burden of design iteration.